Barriers and benefits of on-farm quality assurance system in Western Australia - Liu, A; Batt, Peter (International Society of Horticultural Science, 2011)
Food safety has become an important issue in the developed and developing countries. In order to meet consumers’ increasing needs, many industries are adopting quality assurance systems in order to establish and protect a reputable brand. This paper seeks to identify the barriers and benefits influencing the implementation of onfarm quality assurance systems in Western Australia. For the 178 farmers who participated in the survey, most respondents believed that a quality assurance system would lead to better internal traceability, an improved awareness of food safety and reduce the risk of contamination. The main barriers towards the implementation of a quality assurance system were the increased amount of paperwork and the bureaucracy, the lack of any financial incentive, their ability to sell their grain without a quality assurance system, the lack of time, the high annual cost of certification, the high cost of implementation, and the belief that their customers did not require a quality assurance system.